Gypenosides counteract hepatic steatosis and intestinal barrier injury in rats with metabolic associated fatty liver disease by modulating the adenosine monophosphate activated protein kinase and Toll-like receptor 4/nuclear factor kappa B pathways - Shuhua Shen; Kungen Wang; Yihui Zhi; Yue Dong (Taylor & Francis Group, 2022)
Context Non-alcoholic fatty liver disease (NAFLD), the most common chronic liver disease, can develop into metabolic associated fatty liver disease (MAFLD). Gypenosides (GP), the main phytochemical component of Gynostemma pentaphylla (Thunb.) Makino (Cucurbitaceae), have been applied for treatment of metabolic diseases.Objective We investigate how GP modulate MAFLD-related hepatic steatosis and intestinal barrier injury.Materials and methods In cell experiments, Caco-2 cells were treated with GP (150 or 200 μmol/L, 24 h), following lipopolysaccharide (LPS) exposure (10 μg/mL, 24 h) to mimic MAFLD in vitro. In in vivo experiments, control, model and model + GP groups were set. High fructose diet/high fat (HFD/HF)-fed (12 weeks) MAFLD rats received GP treatment (300 mg/kg, 6 weeks), followed by intra-peritoneal glucose tolerance test and histopathological examination of rat liver and intestinal mucosa using haematoxylin-eosin staining.Results GP at 200 μM significantly reversed LPS-induced decreases in transepithelial electrical resistance (TER) value (25%), protein expression of occludin (two fold) and ZO-1 (four fold), and the ratio of p-AMPK to AMPK (five fold), while partially repressing LPS-induced leakage of FD4 (50%) and LPS-induced increases in the Toll-like receptor 4 (TLR4) level (50%) and the ratio of p-p65 to p65 (55%). Compared with the model rats, rats with GP treatment presented a reduction in gain of weight and glucose tolerance. In addition, GP alleviated HFD/HF-induced histopathological abnormalities in rat liver and intestinal mucosa.Conclusions GP attenuates hepatic steatosis and intestinal barrier injury in MAFLD rats via the AMPK and TLR4/nuclear factor kappa B (NF-κB) pathways, providing a potential treatment for MAFLD patients.